Biodegradable Microsphere-Hydrogel Ocular Drug Delivery System for Controlled and Extended Release of Bioactive Aflibercept In Vitro - Liu, Wenqiang (Curr Eye Res, 2018)
PURPOSE: Current standard of care for neovascular eye diseases require repeated intravitreal bolus injections of anti-vascular endothelial growth factors (anti-VEGFs). The purpose of this study was to validate a degradable microsphere-thermoresponsive hydrogel drug delivery system (DDS) capable of releasing bioactive aflibercept in a controlled and extended manner for 6 months. MATERIALS AND METHODS: The DDS was fabricated by suspending aflibercept-loaded poly(lactic-coglycolic acid) microspheres within a biodegradable poly(ethylene glycol)-co-(L-lactic acid) diacrylate/N-isopropylacrylamide (PEG-PLLA-DA/NIPAAm) thermoresponsive hydrogel. Encapsulation efficiency of DDSs and in vitro release profiles were characterized by iodine-125 radiolabeled aflibercept. The degradation of hydrogel was determined by dry weight changes. The cytotoxicity from degraded DDS byproducts was investigated by quantifying cell viability using LIVE/DEAD® assay. In addition, dot blot and enzyme-linked immunosorbent assay were used to determine the bioactivity of released drug. Finally, morphology of microspheres and hydrogel were investigated by cryo-scanning electron microscopy before and after thermal transformation. RESULTS: The microsphere-hydrogel DDS was capable of releasing bioactive aflibercept in a controlled and extended manner for 6 months. The amount and rate of aflibercept release can be controlled by both the cross-linker concentration and microspheres load amount. The initial burst (release within 24 h) was from 37.35 ± 4.92 to 74.56 ± 6.16 μg (2 and 3 mM hydrogel, each loaded with 10 and 20 mg/ml of microspheres, respectively), followed by controlled drug release of 0.07–0.15 μg/day. Higher PEG-PLLA-DA concentration (3 mM) degraded faster than the lower concentration (2 mM). No significant cytotoxicity from degraded DDS byproducts was found for all investigated time points. Bioactivity of released drug was maintained at therapeutic level over entire release period. CONCLUSIONS: The microsphere-hydrogel DDS is safe and can deliver bioactive aflibercept in a controlled manner. This may provide a significant advantage over current bolus injection therapies in the treatment of ocular neovascularization.